Oxygen integration of autothermal reforming of ethanol with oxygen production, through ion transport membranes in countercurrent configuration - Fischer, Carlos Daniel (2017)
In this work, we propose a new arrangement for integrating an Autothermal Reforming of Ethanol process with oxygen production with the technology of ITM membranes. In the conventional configuration O2is first separated from the air and then injected in the reforming process, while in the new configuration O2is depleted from the air in a counter-current arrangement with a reforming process stream, used as sweep gas. We took from the literature a process for Autothermal Reforming of Ethanol in its optimal operating condition, and scaled it up to pilot size. We assessed the performance of both configurations with Aspen Plus V8.7 and found that the configuration in counter-current arrangement with a process sweep stream has a reduction of the total annualized cost of 27.3% with respect to the conventional separation configuration. Furthermore, we optimize the operating conditions and ancillary structure of the counter-current integrated process, achieving a total annualized cost reduction of 72.2% with respect to the conventional design.